Negotiating Native-Speaker Norms, Accent Diversity, and English Ownership: First-Year it Students' Attitudes Toward English Varieties in the EFL Context - Ismar, Randila Tiayu; Julia Rizki (Indonesian Journal of Teaching and Teacher Education, 2025)
This study examines first-year Information Technology (IT) students' perceptions and attitudes toward English varieties in an English as a Foreign Language (EFL) context, with particular attention to preferences for English varieties, perceptions of accent and pronunciation variation, and beliefs about English ownership and legitimacy. Using a quantitative survey design, data were collected via an online questionnaire comprising 22 Likert-scale items and administered to first-year IT students at an Indonesian university. The findings indicate that students do not hold a single, fixed orientation toward English. While American and British English continue to be associated with academic authority, correctness, and institutional standards, students also demonstrate growing openness toward linguistic diversity, including positive attitudes toward local accents, tolerance for pronunciation variation, and recognition of English as a shared communicative resource. Students' views reflect an ongoing negotiation between established educational norms and the practical demands of global communication, particularly in digital and multilingual environments relevant to the IT field. Rather than a clear shift away from native-speaker norms, the results suggest the emergence of hybrid, context-sensitive orientations, in which different expectations for English are applied depending on communicative purposes. These findings highlight the importance of moving beyond rigid notions of linguistic correctness and support the integration of Global Englishes-informed perspectives in EFL pedagogy, especially in English for Specific Purposes contexts, to better align instruction with students' academic, professional, and communicative needs.